Merchant's card acceptance: An extension of the tourist test for developing countries - Jose Aurazo; Jose Vasquez (Graduate Institute of International and Development Studies, 2019)
This paper extends the tourist test model proposed by Rochet and Tirole (2011) by incorporating the government in order to take into account informality (understood as tax evasion in cash payments) and the net social cost of cash usage. These two elements are relevant in developing countries, where the shadow economy tends to be large and merchants usually evade taxes in cash transactions. The tourist test aims to determine an interchange fee that does not increase merchants' operating cost of accepting card payments. In the presence of informality, the tax gap between card and cash payments reduces merchants' net operating benefit of accepting card sales, which in turn lowers the interchange fee that passes the tourist test. In addition, the interchange fee resulting from the social welfare maximization exceeds this tourist test threshold while the interchange fee that maximizes the total user surplus is still compatible with the tourist test.
Keywords: G21; L11; H26; 330; Tourist test; card payments; tax evasion; developing countries